2017
DOI: 10.1002/pmic.201600323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of targeted proteomics approaches for detecting and quantifying proteins derived from human cancer tissues

Abstract: Targeted mass spectrometry-based proteomics approaches enable the simultaneous and reproducible quantification of multiple protein analytes across numerous conditions in biology and clinical studies. These approaches involve e.g. selected reaction monitoring (SRM) typically conducted on a triple quadrupole mass spectrometer, its high-resolution variant named pseudo-SRM (p-SRM), carried out in a quadrupole coupled with an TOF analyzer (qTOF), and "sequential window acquisition of all theoretical spectra" (SWATH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In Figure 1 row (1), the heatmaps (a) and (b) contrast Affymetrix gene expression data of fresh frozen material of 40 non-Hodgkin lymphomas from ( Klapper et al , 2012 ) to matching nCounter data of FFPE material ( Masqué-Soler et al , 2013 ). The plots in row (2) show proteomics data for 23 of the lymphomas using (a) sequential window acquisition of all theoretical fragment ion spectra (SWATH) ( Gillet et al , 2012 ) and (b) targeted selected reaction monitoring (SRM) ( Faktor et al , 2016 ). For measurement details we refer to the methods section.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1 row (1), the heatmaps (a) and (b) contrast Affymetrix gene expression data of fresh frozen material of 40 non-Hodgkin lymphomas from ( Klapper et al , 2012 ) to matching nCounter data of FFPE material ( Masqué-Soler et al , 2013 ). The plots in row (2) show proteomics data for 23 of the lymphomas using (a) sequential window acquisition of all theoretical fragment ion spectra (SWATH) ( Gillet et al , 2012 ) and (b) targeted selected reaction monitoring (SRM) ( Faktor et al , 2016 ). For measurement details we refer to the methods section.…”
Section: Resultsmentioning
confidence: 99%
“…A strong correlation between SWATH-MS and S/MRM was demonstrated already in the first SWATH-MS publication (Gillet et al, 2012) and confirmed in other independent studies (Kockmann et al, 2016;Liu et al, 2013;Nakamura et al, 2016;Schmidlin et al, 2016). These studies include our recent comparison of S/MRM, pseudo-SRM/MRM HR and SWATH-MS analytical parameters in selected samples from the same breast cancer tissue collection (Faktor et al, 2017). Based on the above data, it has been well demonstrated both experimentally in our breast tumour sample set and in the literature that SWATH-MS provides data highly correlated with S/MRM.…”
Section: Advantages Of Swath-ms To Classify Breast Cancer Tumoursmentioning
confidence: 72%
“…We expect that in the future, more sensitive assays will reveal the now imperceptible quantities of ORF2p. If shotgun proteomic approaches are not sufficient to address ORF2p detection, targeted methods can be developed to maximally leverage the sensitivity of MS instruments (potentially 100s of attomoles [61]). Similarly, approaches such as proximity ligation assays (PLA) or other technologies, may amplify detection by antibodies.…”
Section: Discussionmentioning
confidence: 99%